Pengaruh Model Project Based Learning Terhadap Hasil Belajar Matematika Anak Didik SD Kelas 1 SD Materi Bentuk-Bentuk Bangun - Baiah, Miftahul; Fadiana, Mu'jizatin (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2024)
The purpose of this study is to improve student learning outcomes in the cognitive and psychomotor domains through the application of Project Based Learning learning models. This type of research is classroom action research (CAR). The CAR model used by C. Kemmis & Mc Taggart spiral model was implemented in 2 cycles. Data collection techniques are test techniques and non-test techniques. Research instruments using items and observation sheets. The data analysis technique used is descriptive comparative. Based on the results of the study showed that cognitive domain learning outcomes based on the percentage of pre-cycle learning completeness, cycle I and cycle II amounted to 41.67%; 50%; 75%. While the psychomotor domain learning outcomes based on the percentage of pre-cycle learning completeness, cycle I and cycle II were 50%; 75%; 91.67%. Thus the application of a Project Based Learning model can improve student learning outcomes in the cognitive and psychomotor domains of grade 1 students of SD.